2021
DOI: 10.1177/10126902211032166
|View full text |Cite
|
Sign up to set email alerts
|

Materiality, mediation and affective encounters: ‘Rising Phoenix’ and the cultural representation of disability

Abstract: Paralympic and Para sport representation has provided an important cultural site from which to explore the role of popular disability media in shaping everyday disability knowledge(s) through relations of power, ideology and meaning. Yet limited attention has been afforded to the affective dimensions of Para sport media that may help extend our understanding of its performative power on audiences. In critique of the recent Netflix Paralympic documentary film, ‘Rising Phoenix’, this article affords particular a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…Similarly, Rees et al (2019) found that when disabled athletes are represented in text and print media, they are often represented from a medical model that emphasized diagnosis, or as ‘supercrips’ who have overcome great odds. This often results in a medico-tragedy narrative, that “positions impairment as the result of an unexpected medical problem or pathology” (Pullen, 2022, p. 848), with an emphasis on a need to ‘fix’ the individual in question. Such representations may perpetuate or promote negative stereotypes and understanding of disabled individuals.…”
mentioning
confidence: 99%
“…Similarly, Rees et al (2019) found that when disabled athletes are represented in text and print media, they are often represented from a medical model that emphasized diagnosis, or as ‘supercrips’ who have overcome great odds. This often results in a medico-tragedy narrative, that “positions impairment as the result of an unexpected medical problem or pathology” (Pullen, 2022, p. 848), with an emphasis on a need to ‘fix’ the individual in question. Such representations may perpetuate or promote negative stereotypes and understanding of disabled individuals.…”
mentioning
confidence: 99%